Urban Foodscapes and Greenspace Design: Integrating Grazing Landscapes Within Multi-Use Urban Parks - Davis, Shannon (Frontiers in Sustainable Food Systems, 2021)
Since the early 2000s an increasing number of planning and design projects, within the spatial design fields of landscape architecture and urban design, have focused on food landscapes and their re-integration into the urban environment; particularly as a result of recent global movements toward creating more sustainable cities and human settlements. This article explores the potential contribution of grazing lands within cities of the Global North as a multi-beneficial layer in public greenspace design. Plant-based urban farms and community gardens have experienced significant growth within developed nations in recent years, in both scholarship and practice, however the design and implementation of integrated grazing lands within the urban zone has been largely left out. For much of the Global North animal agriculture is still considered primarily rural. This research considers the potential of integrating grazing lands within the city through multiuse greenspace design, and undertakes a case study design critique of Cornwall Park, Auckland where since 1903, the Park has provided urban grazing for sheep and cattle, alongside other land uses and experiences such as recreation, heritage, bio-diversity, and education. Undertaking a “descriptive critique” of Cornwall Park, and its 100 Year Master Plan, this research is intended to enhance, the understanding and role, grazing animals can play within public greenspace.